Evaluating an iron-based mineral's abrasiveness via a movable rig - Ismail, Issham (Khon Kaen University, 1995)
This paper discusses the utilization of an abrasiveness rig in order to evaluate the abrasiveness effect of Malaysia hematite, an iron-based mineral which has the potential to be used as weighting material in drilling mud. The abrasiveness rig used in this study was developed using an unused laboratory equipment. Two types of test pipes namely copper and aluminium were installed in the rig for abrasiveness test purposes. Experimental results revealed that the Malaysia hematite's rheological properties were found to be comparable to barite, the standard weighting material used in the petroleum industry. Nevertheless, the hematite was found to give higher abrasiveness rate as compared to barite.